The ‘Unsafe’ museum: imagining the Ledra Palace Museum - Stylianou-Lambert, Theopisti; Bounia, Alexandra (My University, 2018)
This presentation offers an introduction to the concept of the “unsafe” museum and provides ways to thinking about the future of museums that deal with difficult heritage. As a case study, we use one of the most controversial sites in Cyprus: the Ledra Palace Hotel. Once praised as the jewel of Cypriot modernity in the heart of its capital, now it is a crumbling dwelling accommodating the United Nations Peacekeeping Force next to the division line between the southern and the northern parts of Cyprus. This specific site is not a museum and there are no current plans to establish a museum. But it is a perfect example of a symbolic, “loaded” building that can be used to negotiate the recent history of conflict in Cyprus. The Ledra Palace Museum will become an imaginary space where - without the practical and political restrictions of an actual museum - we can re-imagine the future of museums that deal with difficult heritage.
Keywords: Museums; Heritage